Are Pegged and Intermediate Regimes More Crisis Prone? - Bubula, Andrea; Otker, Inci. (Washington, D.C. : International Monetary Fund, 2003)
This paper provides evidence on the susceptibility of different types of exchange rate regimes to currency crises during 1990-2001. It explores the incidence of crises, identified as episodes of severe exchange market pressure, to seek evidence on whether pegged regimes are more crisis prone than floating regimes and on whether certain types of pegged regimes are more crisis prone than others. The paper finds that pegged regimes, as a whole, have been characterized by a higher incidence of crises than floating regimes, for countries that are more integrated with international capital markets; and that intermediate regimes (mainly soft pegs and tightly-managed floating regimes) have been more crisis prone than both hard pegs and other floating regimes-a view consistent with the bipolar view of exchange rate regimes. The degree of crisis proneness seems to be broadly similar across different types of intermediate regimes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet